Fluctuation-induced modifications of the phase structure in (2+1)-flavor QCD - Rennecke, Fabian; Schaefer, Bernd-Jochen (Physical review, 2017)
The low-energy sector of QCD with Nf=2+1 dynamical quark flavors at nonvanishing chemical potential and temperature is studied with a nonperturbative functional renormalization group method. The analysis is performed in different truncations in order to explore fluctuation-induced modifications of the quark-meson correlations as well as quark and meson propagators on the chiral phase transition of QCD. Depending on the chosen truncation, significant quantitative implications on the phase transition are found. In the chirally symmetric phase, the quark flavor composition of the pseudoscalar (η,η′)-meson complex turns out to be drastically sensitive to fluctuation-induced modifications in the presence of the axial U(1)A anomaly. This has important phenomenological consequences for the assignment of chiral partners to these mesons.
Gesehen am 22.05.2018